WACANA KELESTARIAN ALAM CERITA LIPI SELAN BUKIT PADA MASYARAKAT ADAT TENGANAN PEGERINGSINGAN - Ari Mahayu, Ni Putu Coryna (Humanis; Volume 11. No2. Mei 2015, 2015)
This study discusses the Discourse of Nature Conservation Story Lipi Selan Bukit Indigenous In Tenganan Pegeringsingan the study of form, function and meaning. Lipi Selan Bukit story comes from the village of Tenganan Pegeringsingan. The reasons for selecting this title dianataranya is (1) because the studies have not been investigated (2) interesting story (3) because the origin of this story comes from thevillageitself. Discourse of Nature Conservation Story Lipi Selan Bukit Indigenous In Tenganan Pegeringsingan analyzed using structural theory, the theory of semiotics and discourse theory. Structural theory relating to the structure at the level of literary works (intrinsic), and the level of the system is contained in the Discourse of Nature Conservation Story Lipi Selan Bukit Indigenous In Pegeringsingan Tenganan. The theory uses a combination of some of them Wiyatmi literary expert opinion, Sukada, Luxemburg, Damono. The methods used can be divided into three stages, the first stage of data provision, in this first stage is used idiomatically followed the literal translation method using read something about assisted with recording techniques. Second, the data processing stage, in this stage used analytical descriptive method assisted with recording techniques, and the third is the presentation of the results of the data analysis stage, in this stage is used informal methods. Disclosure of structure Discourse Nature Lipi Selan Bukit Conservation Story In Tenganan Indigenous Pegeringsingan in units of the form include: prose, language diversity, language style. While the unit structure of narrative disclosures include: character and characterization, plot, incidents, setting, theme, mandate. Discourse Analysis of semiotics in Nature Conservation Story Lipi Selan Bukit Indigenous In Tenganan Pegeringsingan, includes elements of the function and meaning contained in the discourse. Functions include: natural sustainable, prosperous communities. While meanings include: Tri Hita Karana, Social Institution.
Keywords: form, function, and meaning.